2007
DOI: 10.1111/j.1365-2710.2007.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of hydrogen peroxide-based antiseptic solutions available in Dar es Salaam, Tanzania

Abstract: A significant proportion of hydrogen peroxide products in the Dar es Salaam market is of poor quality. There is a need for continuous monitoring of the quality of hydrogen peroxide available in the city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The resulting superoxide and hydroxyl radicals led to the formation of molecular oxygen. The influence of acids on H 2 O 2 decomposition is also known, and various mineral acids have been used to stabilize H 2 O 2 . ,, In addition, Hutchings and co-workers have found that an acid pretreatment of carbon supports for Au/Pd catalysts increases the yield of H 2 O 2 production from hydrogen and oxygen . In this context, note that acids could lead to leaching of Ti by protonolysis reactions of Ti–O–Si linkages in the catalytic materials.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting superoxide and hydroxyl radicals led to the formation of molecular oxygen. The influence of acids on H 2 O 2 decomposition is also known, and various mineral acids have been used to stabilize H 2 O 2 . ,, In addition, Hutchings and co-workers have found that an acid pretreatment of carbon supports for Au/Pd catalysts increases the yield of H 2 O 2 production from hydrogen and oxygen . In this context, note that acids could lead to leaching of Ti by protonolysis reactions of Ti–O–Si linkages in the catalytic materials.…”
Section: Discussionmentioning
confidence: 99%